Maize ZmbZIP33 Is Involved in Drought Resistance and Recovery Ability Through an Abscisic Acid-Dependent Signaling Pathway - Cao, Liru; Lu, Xiaomin; Wang, Guorui; Zhang, Qianjin; Zhang, Xin; Fan, Zaifeng; Cao, Yanyong; Wei, Li; Wang, Tongchao; Wang, Zhenhua (Frontiers in Plant Science, 2021)
Analyzing the transcriptome of maize leaves under drought stress and rewatering conditions revealed that transcription factors were involved in this process, among which ZmbZIP33 of the ABSCISIC ACID-INSENSITIVE 5-like protein 5 family was induced to significantly up-regulated. The functional mechanism of ZmbZIP33 in Abscisic acd (ABA) signaling pathway and its response to drought stress and rewatering has not been studied yet. The present study found that ZmbZIP33 contains a DNA-binding and dimerization domain, has transcriptional activation activity, and is highly homologous to SbABI1,SitbZIP68 and OsABA1.The expression of ZmbZIP33 is strongly up-regulated by drought, high salt, high temperature and ABA treatments. Overexpression of ZmbZIP33 remarkably increased chlorophyll content and root length after drought stress and rewatering,moreover,cause an accumulation of ABA content, thereby improving drought resistance and recovery ability in Arabidopsis. However,silencing the expression of ZmbZIP33 (BMV-ZmbZIP33) remarkably decreased chlorophyll content, ABA content, superoxide dismutase and peroxidase activities，and increased stomatal opening and water loss rate compared with BMV (control). It showed that silencing ZmbZIP33 lead to reduced drought resistance and recovery ability of maize. ABA sensitivity analysis found that 0.5μmol/L and 1μmol/L treatments severely inhibited the root development of overexpression ZmbZIP33 transgenic Arabidopsis. However,the root growth of BMV was greatly inhibited for 1μmol/L and 5μmol/L ABA treatments,but not for BMV-ZmbZIP33.Subcellular localization, yeast two-hybrid and BIFC further confirmed that the core components of ABA signaling pathways ZmPYL10 and ZmPP2C7 interacted in nucleus, ZmPP2C7 and ZmSRK2E as well as ZmSRK2E and ZmbZIP33 interacted in the plasma membrane. We also found that expression levels of ZmPYL10 and ZmSRK2E in the BMV-ZmbZIP33 mutant were lower than those of BMV, while ZmPP2C7 was the opposite under drought stress and rewatering. However,expression of ZmPYL10 and ZmSRK2E in normal maize leaves were significantly up-regulated by 3~4 folds after drought and ABA treatments for 24h,while ZmPP2C7 was down-regulated.The NCED and ZEP encoding key enzymes in ABA biosynthesis are up-regulated in overexpression ZmbZIP33 transgenic line under drought stress and rewatering conditions,but down-regulated in BMV-ZmbZIP33 mutants.Together, these findings demonstrate that ZmbZIP33 played roles in ABA biosynthesis and regulation of drought response and rewatering in Arabidopsis and maize thought an ABA-dependent signaling pathway.